P3 4 A Near Fatal Lecture - Brewer, Lois; Bates, Ethan; Sadler, Tommy; Smith, Kennedy (Physics Special Topics, 2022)
Despite rising carbon dioxide levels, it is not currently high enough to cause any long-term effects on the body. There is no common consensus as to what concentrations of CO2 can cause hypercapnia, but this tends to occur at concentrations greater than 5%, with levels of over 10% often leading to fatalities [1]. We investigate how long it would take for a typical lecture hall to reach this 5% critical level, which begins to affect consciousness, with a standard physics cohort just by breathing, which we find this length of time is around 6.5 hours.